Method for extraction of lutein from marigold - YANG YANG (2017)
The invention provides a method for extraction of lutein from marigold. The method includes: fermentation, enzymolysis, supercritical CO2 extraction and vacuum freeze drying. The method has the beneficial effects that: through fermentation of Angel yeast powder, lutein ester is converted into free lutein, saponification reaction is replaced, and the conversion rate of free lutein is high; the enzyme method destroys the cell structure completeness, more substances in cells can be exposed during extraction, thus increasing oil permeability. Enzymatic degradation of marigold flowers does cause isomerization of lutein, and the enzyme treated marigold powder has a high content of all-trans lutein; and the finally obtained lutein has high purity, high content of all-trans lutein and strong antioxidant properties, is green and healthy, and can be used for food, medicine, cosmetics fields. 本发明提供了种从万寿菊中提取叶黄素的方法，包括发酵、酶解、超临界CO萃取、真空冷冻干燥。有益效果为：通过安琪酵母粉发酵将叶黄素酯转化为游离的叶黄素，代替了皂化反应，游离的叶黄素转化率高；酶法破坏细胞结构的完整，使萃取时细胞内的物质更多暴露出来，增加油的渗透性